The important of typography in publication / Nur Eirza Khairunnisa Mohd Rezan - Mohd Rezan, Nur Eirza Khairunnisa (Faculty of Art and Design, 2020)
Typography plays an integral part in design and publication. In the modern era. the audience is aware of typography. design and others. Typography is used as a more extensive conversation to global visual culture, and the audience starts to increasingly aware of the effects of visual design. Typography is used as letter design in print or digital media. Also bring definition to giving text form and its sense of wonder, (Danielle, 2014). The unique font would add character and relate to the body text, and the reader may notice the typeface faster. Typography is often used to attract the reader. Usually. the reader is quickly drawn to something new, unique and not commonly seen. The typeface was category under typography. There is a different type of typeface and typeface gives a fresh font and a new look. In education publication, typography is essential to attract the reader to continue reading and also grab reader attention so that the reader will not be bored. Typography is essential to keep the reader being interested in learning education publication. There are six different typeface sorting, that is a serif, San-serif - mono spaced, cursive, fantasy, and script. The most commonly used is serif and San-serif. Education publication can be more interested in having an exciting info graphic and fonts (Nathan, 2014)